(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to determine the effect of chicken manure dosage and eco-enzyme concentration on the growth and yield of yardlong bean (Vigna sinensis L.). The research was conducted in March 2024 at the Experimental Farm of the Faculty of Agriculture, Universitas Pembinaan Masyarakat Indonesia (UPMI), Medan, using a factorial Randomized Complete Block Design (RCBD) with two factors: chicken manure dosage (0, 20, 40, and 80 tons ha⁻¹) and eco-enzyme concentration (0, 10, 20, and 30 mL L⁻¹ of water), with three replications. The observed parameters included plant height at 14–35 days after planting (DAP) and pod weight per sample at the end of the observation period. The data were analyzed using analysis of variance (ANOVA) at a 95% confidence level (α = 0.05) to determine the effects of treatments and their interaction. When significant differences were detected, mean comparisons were performed using Duncan’s Multiple Range Test (DMRT) at the 5% significance level. The results of the analysis of variance indicated that neither chicken manure dosage nor eco-enzyme concentration had a significant effect on plant height or pod weight per sample. Furthermore, no significant interaction was observed between the two treatments for all measured parameters. These findings indicate that, under the conditions of this study, the application of chicken manure and eco-enzyme at the tested dosages was not able to significantly improve the growth and yield of yardlong bean. Therefore, further studies are recommended to evaluate appropriate dosages, application timing, and soil conditions to obtain a more optimal crop response.